Improved Localization and Detection of Nodes in VANET - Kurian, Simy Mary; Sainudeen, Jinu P; Sujitha, M; Joseph, Neena (International Journal of Computer Sciences and Engineering, 2025)
In present day world, the quantities of vehicles are expanding eccentrically and therefore mishaps, criminal traffic offenses; vehicle robbery and so forth additionally expanded a ton. Following definite area of every vehicle (hub) might be helpful in taking care of numerous such issues. From metropolitan to provincial the thickness of traffic, width of the street, network inclusion and so forth might change; this makes confinement of vehicle a difficult errand. The development of transport framework doesn't give a genial answer for these issues and here and there it even makes such issues more serious. This paper centers around the review of area discovery for every vehicle as well concerning the walkers alongside different directing procedures in a VANET